Hypertension linked to allostatic load: from psychosocial stress to inflammation and mitochondrial dysfunction. (4th March 2019) - Mocayar Marón, Feres José; Ferder, León; Saraví, Fernando Daniel; Manucha, Walter
Abstract: Although a large number of available treatments and strategies, the prevalence of cardiovascular diseases continues to grow worldwide. Emerging evidence supports the notion of counteracting stress as a critical component of a comprehensive therapeutic strategy for cardiovascular disease. Indeed, an unhealthy lifestyle is a burden to biological variables such as plasma glucose, lipid profile, and blood pressure control. Recent findings identify allostatic load as a new paradigm for an integrated understanding of the importance of psychosocial stress and its impact on the development and maintenance of cardiovascular disease. Allostasis complement homeostasis and integrates behavioral and physiological mechanisms by which genes, early experiences, environment, lifestyle, diet, sleep, and physical exercise can modulate and adapt biological responses at the cellular level. For example, variability is a physiological characteristic of blood pressure necessary for survival and the allostatic load in hypertension can contribute to its related cardiovascular morbidity and mortality. Therefore, the current review will focus on the mechanisms that link hypertension to allostatic load, which includes psychosocial stress, inflammation, and mitochondrial dysfunction. We will describe and discuss new insights on neuroendocrine-immune effects linked to allostatic load and its impact on the cellular and molecular responses; the links between allostatic load, inflammation, and endothelial dysfunction; the epidemiological evidence supporting the pathophysiological origins of hypertension; and the biological embedding of allostatic load and hypertension with an emphasis on mitochondrial dysfunction.